Biallelic disruption of DDX41 activity is associated with distinct genomic and immunophenotypic hallmarks in acute leukemia - Tierens, Anne; Kagotho, Elizabeth; Shinriki, Satoru; Seto, Andrew; Smith, Adam C.; Care, Melanie; Maze, Dawn; Sibai, Hassan; Yee, Karen W.; Schuh, Andre C.; Kim, Dennis Dong Hwan; Gupta, Vikas; et al. (Frontiers in Oncology, 2023)
Introduction. Inherited DDX41 mutations cause familial predisposition to hematologic malignancies including acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS), with the majority of DDX41 mutated MDS/AMLs described to date harboring germline DDX41 and co-occurring somatic DDX41 variants. DDX41-AMLs were shown to share distinguishing clinical features such as a late AML onset and an indolent disease associated with a favorable outcome. However, genotype-phenotype correlation in DDX41-MDS/AMLs remain poorly understood. Methods. Here, we studied the genetic profile, bone marrow morphology and immunophenotype of 51 patients with DDX41 mutations. We further assessed the functional impact of ten previously uncharacterized DDX41 variants of uncertain significance. Results. Our results demonstrate that MDS/AML cases harboring two DDX41 variants share specific clinicopathologic hallmarks that are not seen in other patients with monoallelic DDX41 related hematologic malignancies. We further showed that the features seen in these individuals with two DDX41 variants were concordant with biallelic DDX41 disruption. Discussion. Here, we expand on previous clinicopathologic findings on DDX41 mutated hematologic malignancies. Functional analyses conducted in this study unraveled previously uncharacterized DDX41 alleles and further illustrate the implication of biallelic disruption in the pathophysiology of this distinct AML entity.